The different other – towards an including ethics of care - Myhrvold, Trine (Nursing philosophy, 2006)
The aim of this article is to continue the discussion about factors of importance for an including ethics of care. A further polarization between partiality and impartiality does not seem a relevant approach. What is important is to direct attention both to the other and to the third person, which requires an acknowledgement of responsibility that extends beyond established relationships. Thus, we need to draw attention not only to the vulnerability existing within every seriously ill or injured person, but to factors of importance for marginalization of groups like refugees, people suffering from serious mental illness, and substance misusers, to mention some in the Western world. Marginalized groups are groups experiencing a discrepancy between need of health care and care given. They are not given proper priority in the distribution of resources, and they may experience ignorance when they first meet the healthcare system as patients. Efforts to understand what circumstances can lead to inadequate inclusion indicate that the elements of differentness and extensive losses of life contexts which may be causing feelings of hopelessness and helplessness in the health professionals, are key factors posing challenges to empathy both within and beyond established relationships, besides geographical distance. Groups of people who have suffered extensive loss in their life contexts may be threatening for us, as they reflect our own fears, and remind us of our own vulnerability. I raise the question: How can we contribute to meeting the need for an ethics of care that extends beyond the familiar to the unfamiliar both in established and non-established relationships?